Postoperative Complications of Beger Procedure - Nayana Samejima Peternelli; Tali Wajsfeld; Felipe Henrique Yazawa Santos; Otavio Schmidt de Azevedo; Rodrigo Altenfelder Silva; Adhemar Monteiro Pacheco Junior (Case Reports in Surgery)
Introduction. Chronic pancreatitis (CP) is considered an inflammatory disease that may cause varying degrees of pancreatic dysfunction. Conservative and surgical treatment options are available depending on dysfunction severity. Presentation of Case. A 36-year-old male with history of heavy alcohol consumption and diagnosed CP underwent a duodenal-preserving pancreatic head resection (DPPHR or Beger procedure) after conservative treatment failure. Refractory pain was reported on follow-up three months after surgery and postoperative imaging uncovered stones within the main pancreatic duct and intestinal dilation. The patient was subsequently subjected to another surgical procedure and intraoperative findings included protein plugs within the main pancreatic duct and pancreaticojejunal anastomosis stricture. A V-shaped enlargement and main pancreatic duct dilation in addition to the reconstruction of the previous pancreaticojejunal anastomosis were performed. The patient recovered with no further postoperative complications in the follow-up at an outpatient clinic. Discussion. Main duct and pancreaticojejunal strictures are an unusual complication of the Beger procedure but were identified intraoperatively as the cause of patient’s refractory pain and explained intraductal protein plugs accumulation. Conclusion. Patients that undergo Beger procedures should receive close outpatient clinical follow-up in order to guarantee postoperative conservative treatment success and therefore guarantee an early detection of postoperative complications.